End-of-Life-Care Quality in ICUs Is Associated With Family Surrogates' Severe Anxiety and Depressive Symptoms During Their First 6 Months of Bereavement*. Issue 1 (January 2021) - Tang, Siew Tzuh; Huang, Chung-Chi; Hu, Tsung-Hui; Lo, Mei-Ling; Chou, Wen-Chi; Chuang, Li-Pang; Chiang, Ming Chu
Abstract : OBJECTIVES: Evidence linking end-of-life-care quality in ICUs to bereaved family members' psychologic distress remains limited by methodological insufficiencies of the few studies on this topic. To examine comprehensively the associations of family surrogates' severe anxiety and depressive symptoms with end-of-life-care quality in ICUs over their first 6 months of bereavement. DESIGN: Prospective, longitudinal, observational study. SETTING/PARTICIPANTS: Family surrogates ( n = 278) were consecutively recruited from seven medical ICUs at two academically affiliated medical centers in Taiwan. MEASUREMENTS AND STATISTICAL ANALYSIS: Family surrogates' anxiety and depressive symptoms were assessed 1, 3, and 6 months postloss using the Hospital Anxiety and Depression Scale. Family satisfaction with end-of-life care in ICUs was assessed 1-month postloss by the Family Satisfaction in the ICU questionnaire. Patients' end-of-life care was documented over the patient's ICU stay. Associations of severe anxiety and depressive symptoms (scores ≥ 8 for each subscale) with end-of-life-care quality in ICUs (documented by patient care received and family satisfaction with end-of-life care in ICUs) were examined by multivariate logistic regression models with generalized estimating equation. MAIN RESULTS: Prevalence of severe anxiety and depressive symptoms decreased significantly over time. Surrogates' lower likelihood of severe anxiety or depressive symptoms 3–6 month postloss was associated with death without cardiopulmonary resuscitation, withdrawing life-sustaining treatments, and higher family satisfaction with end-of-life care in ICUs. Bereaved surrogates' higher likelihood of these symptoms was associated with physician-surrogate prognostic communication and conducting family meetings before patients died. CONCLUSIONS: End-of-life-care quality in ICUs is associated with bereaved surrogates' psychologic well-being. Enhancing end-of-life-care quality in ICUs by improving the process of end-of-life care, for example, promoting death without cardiopulmonary resuscitation, withdrawing life-sustaining treatments, and increasing family satisfaction with end-of-life care, can lighten bereaved family surrogates' severe anxiety symptoms and severe depressive symptoms.